International Expansion Strategy of Japanese Firms: Capability Building through Sequential Entry - Chang, Sea‐Jin (Academy of Management Journal, 1995)
This study empirically investigates the sequential entry process of Japanese electronic manufacturing firms into the United States during l976-89. We find that firms sequentially enter businesses where they have a stronger competitive advantage over locals and core businesses first in order to reduce the hazard of failure. The learning from early entry enables firms to launch a further entry into an area of less strong competitive advantage. The overall evidence in this paper suggests that firms are building capabilities to operate overseas through sequential entry.